Analisis Kemapuan Berpikir Kritis Siswa SMP berbasis Gaya Kognitif melaui Pembelajaran TPS (Think Pairs Share) dengan Media Poster - Rahayu, Rahayu; Cintamulya, Imas (Bioedukasi: Jurnal Pendidikan Biologi, 2019)
The demand for curriculum 2013 requires students to think critically in the learning process. However, the current process of learning in schools about the aspect of critical thinking has not been empowered. In addition, another aspect that has also not been considered is the cognitive style of students. The cognitive style of the students shows the variation of student learning styles. The purpose of this research is to describe critical thinking based on reflective and impulsive cognitive style on students of SMP Muhammadiyah 15 Sedayulawas class VII-B in biology study of environmental pollution subject through Think Pairs Share model and poster media. This research is a descriptive explorative research type. Subjects in this study were students of SMP Muhammadiyah 15 Sedayulawas class VII-B consisting of 9 students of reflective cognitive style and 9 students of cognitive impulsive style. Data of critical thinking ability was obtained from the critical thinking test sheet of critical thinking indicator which refers to bloom taxonomy on C3 (Applied) and C4 (Analysis) level, while cognitive style data obtained from cognitive style test refers to known cognitive style test instrument (MFFT).Data analysis technique of critical thinking ability in non parametric statistical analysis with Mann Whitney test. For analysis of cognitive style data obtained by Matching Familiar Figures Test (MFFT) test. From the results of data analysis, students with reflective cognitive styles have higher critical thinking skills compared to students of impulsive cognitive styles. Based on the result of the research, it can be concluded that the students' critical thinking ability with reflective cognitive style is better than the cognitive impulsive students after through the TPS (Think Pairs Share) learning model combined with the poster media